Oral History as a Methodology of Research in Folkcommunication (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT We discussed Oral history as an investigative possibility for scientific research in Folkcommunication. The goal is to present relevance as a methodology and to strengthen its interdisciplinary perspective. Thus, there is an approximation between the Folkcommunication with Oral history, discussing some theoretical aspects and about its methodological possibilities, as well as reflections on memory, Orality and identity construction. KEY-WORDS Folkcommunication; Oral history; Social memory; Research methodology; Interdisciplinarity.